Sensibilidad francesa en el contexto educativo “socialista” de los años 1930 en México - Estela MUNGUÍA ESCAMILLA (Les Cahiers ALHIM)
Traditionally, education in Mexico, throughout all its different levels, has been in the hands of public institutions which depend on local and private financing. Among the latter we can find  French schools. The purpose of this work is to highlight the French community’s reaction to the vicissitudes their schools had to overcome as a result of the reform of the Third Constitutional Article in the 1930s. This Article established what is now refered to as “socialist education” and this model shaped the immediate future of these institutions as well as the teachers’. They were obliged to overcome the difficulties posed by the new educative reform, and by the people who were in charge of its implementation, They had to do so in a “sensitive” way and according to their own possibilities, by changing their work dynamics inside their schools or by working underground. Their sole purpose was to maintain and continue their formative and cultural labor in Mexico.